2019
DOI: 10.1590/1809-4430-eng.agric.v39n5p649-658/2019
|View full text |Cite
|
Sign up to set email alerts
|

Price and Quality of Coffee (Coffea Arabica L.) Dried Using Air Dehumidified by Convection

Abstract: Grain drying processes have been improved to reduce costs and losses of coffee beverage quality. The objectives of this study were to evaluate the quality of coffee dried using air partially dehumidified before entering drying units (DUs) in four coffee-producing farms, as well as the effects of such process on coffee commercial value. The method consisted of obtaining three samples (triplicates) of coffee dried in both DUs and concrete terraces (control) for mean multiple comparisons. The following variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The criteria corresponding to the second hierarchical structure level are the percent of extrinsic defects, loss in precleaning, price, and taste. This is similar to the study by Konopatzki et al (2019), who used the defect number, cupping test, and pricing as variables to study the price and quality of coffee dried dehumidification by convection.…”
Section: Establish Relevant Criteriamentioning
confidence: 55%
“…The criteria corresponding to the second hierarchical structure level are the percent of extrinsic defects, loss in precleaning, price, and taste. This is similar to the study by Konopatzki et al (2019), who used the defect number, cupping test, and pricing as variables to study the price and quality of coffee dried dehumidification by convection.…”
Section: Establish Relevant Criteriamentioning
confidence: 55%
“…The fruits of the harvested coffee were distributed between the concrete yard and the DU (see Figure 1). Source: Adapted from Konopatzki et al (2019); Barreto (2012) and Barreto (2013).…”
Section: Methodsmentioning
confidence: 99%
“…The quality of dry coffee with partially dehumidified air was presented by Konopatzki et al (2019). In their study the authors used electric coffee drying units (DUs) and concluded that the dry product in DUs has a higher quality of beverage and reaches a higher market value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation